2020
DOI: 10.4103/ijpc.ijpc_157_19
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high-fidelity simulation in nursing education for end-of-life care: A quasi-experimental design

Abstract: Background: Providing end of life (EOL) care is a component of palliative care but dealing with dying patients and their family members is stressful for the healthcare providers. To prepare them for providing EOL care, the high-fidelity simulation could be used as a pedagogy in which real-life scenarios are used on the computerized manikins mimicking the real patients. Aims: The aim of this study was to measure the effectiveness of high-fidelity simulation to teach EOL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…This simulation forced them to develop confidence in addressing caregiver concerns, in addition to patient concerns, by being more cognizant of these. This same phenomenon was also found among participants in a study where participants also stated they were more likely to provide care to family members after simulation 22 and where participants demonstrated significantly improved psychological care skills post simulation. 23 Communication with caregivers created an emotional response, and participants reflected that this "affected" them, in some cases even more than communicating with the patient.…”
Section: Caregivers Need To Be Seen and Heardsupporting
confidence: 65%
“…This simulation forced them to develop confidence in addressing caregiver concerns, in addition to patient concerns, by being more cognizant of these. This same phenomenon was also found among participants in a study where participants also stated they were more likely to provide care to family members after simulation 22 and where participants demonstrated significantly improved psychological care skills post simulation. 23 Communication with caregivers created an emotional response, and participants reflected that this "affected" them, in some cases even more than communicating with the patient.…”
Section: Caregivers Need To Be Seen and Heardsupporting
confidence: 65%
“…Some studies have reported similar results using FATCOD [21] and FATCOD-B [11,22,23]. However, these studies mostly used mixed methods: a speci c educational program [10], an online multimedia training program [21,22], and simulation [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further learning opportunities may be needed to effect changes in attitudes toward dying patients. In addition, the de nitions and correspondence of subscales in the factor analysis in translating the FATCOD-B are different in the palliative/EOL studies, and most studies did not conduct further subscale analysis [21,23,27,28]. Although the Japanese version of Nakai et al's [13] factor analysis indicated three factors, "attitudes toward death" is a single item.…”
Section: Discussionmentioning
confidence: 99%
“…In simulated learning, the learner participates in a scenario as if the situation were occurring, thereby allowing the learner to react naturally. A consensus is well documented of the benefits of simulation as a teaching strategy as one that enhances clinical skills and clinical judgment (Bowen-Withington et al, 2020; Rattani et al, 2020; Sedgwick et al, 2021). In a study evaluating the impact of three different approaches to ethics education, Gallagher et al (2017) noted that an immersive live simulation experience increased ethical sensitivity and ethical action.…”
Section: Teaching Strategies For Ethics Educationmentioning
confidence: 99%